Interior Materiality - Guler, Kutay (Open textbook library., 2024)
The knowledge of materials and finishes is the bridge that links conceptual design to real-world application. It is among the core content of virtually all interior architecture/design curricula, moreover, access to up-to-date information on emerging technologies and trends is a key exigency for the contemporary designer. Accordingly, this book is authored to form a comprehensive resource for the “hows” and “whys” surrounding the functional and aesthetic contributions of a wide selection of materials and finishes used in multiple spatial design contexts. The knowledge base presented here is not only useful in shaping spatial experience, ensuring occupant well-being, and employing sustainable thinking but also beneficial in managing budget and schedule while enabling the delivery of top-quality work. The book investigates fundamental material properties, performance criteria, as well as sector-specific standards, regulations, and guidelines, with a special focus on concerns surrounding occupant health and safety as well as environmental impact and sustainability concerns. Furthermore, fabrication, installation, and maintenance issues were explored in detail. Various information collection and organization conventions are also discussed with regard to detailing, specification, estimation, and documentation of materials and finishes.